Aerodynamics of airfoil sections and their influence on wind turbine design and performance - Abdelrahman, Mohammad; Hassanein, Atef (2011)
The primary goal of this work is to reflect the effectiveness of the aerodynamic characteristics of blade airfoil-sections on the design and overall performance predictions of the horizontal-axis wind turbines. The significant requirements that should be satisfied by the airfoil sections used in this type of wind turbines are explored and discussed. A post-stall model has been introduced and used throughout the work to secure reliable data in a wide range of angles of attack. A sensitivity analysis has been established through the selection of airfoil sections with different aerodynamic characteristics at the main stations along the blade (tip, mid, and root) in addition to the replacement of the whole blade with another one having different airfoil sections. It has been found that the general performance requirement of such airfoils is to exhibit a maximum lift-coefficient which is relatively insensitive to roughness effects and to have a low minimum drag coefficient and/or a high lift/drag ratio. The contribution of these parameters at the blade-tip region is very high and almost equal to the contributions of the mid and root regions together. Consequently, the airfoil section should be designed/selected according to its location along the blade to ensure its highest contribution to the overall performance of the rotor.